Extreme ischaemic heart disease risk in people with type 1 diabetes - Herrington, W; Bragg, F (BMJ Publishing Group, 2017)
Observational epidemiology shows strong associations between diabetes and risk of ischaemic heart disease (IHD).Data, mainly from population-based cohorts in high-income countries, suggest diabetes doubles the risk of IHD, and this association may be doubled again in countries where healthcare resources to treat diabetes are limited. Diabetes associates with several known cardiovascular disease risk factors, but the persistence of this excess risk despite accounting for the effects of blood pressure, lipids and lifestyle factors including smoking, suggests other important mediators of risk exist.